2022
DOI: 10.21203/rs.3.rs-1606215/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Underestimated effect of antiphospholipid antibodies on arteriovenous fistula maturation in hemodialysis patients

Abstract: Background: Arteriovenous fistula delay or absence of maturation is a common problem in hemodialysis. The prevalence of antiphospholipid antibody is higher among hemodialysis patients compared to the general population and is inconsistently associated with arteriovenous fistula thrombosis or stenosis. However, the effect of antiphospholipid antibodies on delayed or absence of maturation of the arteriovenous fistula has never been studied. Methods: We retrospectively identified 103 hemodialyzed patients with ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Interestingly, this subgroup of patients had significantly higher maturation failure rates compared to aPL negative patients. This study was designed to assess AVF thrombosis or stenosis, only during the AVF maturation period (i.e., a 6-week period) [ 48 ].…”
Section: Interpretation and Limitation Of Apl Positivity In Hd Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this subgroup of patients had significantly higher maturation failure rates compared to aPL negative patients. This study was designed to assess AVF thrombosis or stenosis, only during the AVF maturation period (i.e., a 6-week period) [ 48 ].…”
Section: Interpretation and Limitation Of Apl Positivity In Hd Patientsmentioning
confidence: 99%
“…This association was independent of stenosis and intimal hyperplasia in a multivariate analysis. Interestingly, we reported that patients with a fluctuation aPL profiles also have a significant higher prevalence of AVF maturation failure [ 48 ]. We hypothesized that aPL might cause AVF maturation failure, possibly through endothelial dysfunction leading to an impaired vascular remodeling capability without stenosis [ 7 , 59 , 60 ].…”
Section: Antiphospholipid Mediated Avf Complicationsmentioning
confidence: 99%